Accidents at work and its impact on a hospital in Northern Portugal Accidentes de trabajo y su impacto en un hospital en el norte de Portugal Acidentes de trabalho e suas repercussões num hospital ao Norte de Portugal - Matilde Delmina da Silva Martins; Norberto Anibal Pires da Silva; Teresa Isaltina Gomes Correia (Universidade de São Paulo, 2012)
In order to describe accidents at work at a hospital in Northern Portugal and analyze their main impact in the period from 2008 to 2010, we conducted a retrospective cross-sectional study. The information was obtained from the notification records of accidents at work for 387 workers. The highest prevalence levels of accidents referred to superior health technician (56.1%), female workers (81.9%), in the age group 30-39 years (37.2%), with a secondary education degree (55.8%), working in shifts (72.4%) and in-patient services (35.9%). Needle pricks were the main cause (45.7%) and hands were the main injury location (37.5%). Wounds (32.6%) were the most frequent type of injury, followed by sprains and strains (23%). In total, 27.4% resulted in absence from work, with sprains and strains as the main reason. Preventive strategies should be adopted, aiming to promote these workers' health. Para describir los accidentes de trabajo en un hospital del norte de Portugal y analizar su impacto principal en período 2008 a 2010, se realizó un estudio retrospectivo de corte transversal. La información se obtuvo mediante la notificación de registro de accidentes de trabajo de 387 trabajadores. La mayor prevalencia de accidentes cayó en los técnicos superiores de salud (56,1%), en el sexo femenino (81,9%), con edad 30-39 años (37,2%), con la educación superior a los 12 años (55,8%), trabajando en turnos (72,4%) y servicios de hospitalización (35,9%). La causa principal fue el pinchazo de aguja (45,7%) y la lesión se produjo principalmente en las manos (37,5%). Las heridas (32,6%) fueran el tipo más frecuente de lesión. Dieron lugar a la ausencia del trabajo 27,4%, con esguinces y distensiones la principal razón. Las estrategias preventivas deben ser adoptadas con miras a la promoción de la salud de los profesionales. Com o objetivo de descrever os acidentes de trabalho num hospital ao Norte de Portugal e analisar as suas principais repercussões, no período de 2008 a 2010, realizou-se este estudo transversal retrospectivo. A informação foi obtida recorrendo-se ao registro de notificação dos acidentes de trabalho, referentes a 387 trabalhadores. A maior prevalência de acidentes recaiu nos técnicos superiores de saúde (56,1%), em trabalhadores do gênero feminino (81,9%), no grupo etário entre 30 e 39 anos (37,2%), com escolaridade superior ao 12º ano (55,8%), trabalhando por turnos (72,4%) e nos serviços de internamento (35,9%). A principal causa de acidentes foi a picada de agulha (45,7%) e a lesão mais prevalente verificou-se nos membros superiores (43,2%). As feridas representaram o tipo de lesão mais frequente (32,6%), resultando em ausência ao trabalho (27,4%), sendo as entorses/distensões o principal motivo. Estratégias preventivas devem ser adotadas objetivando a promoção da saúde desses profissionais.